South and North, East and West : The Oxfam Book of Children's Stories - Edited by Rosen, Michael (London Walker Books, 2007)
Collected from London school children or discovered in the country of origin by Oxfam field workers, this anthology includes international stories - from countries including Botswana, Indonesia, Jamaica, Vietnam, India and Brazil - illustrated by contemporary artists.
Include Color Illustration
Keywords: Tales -- Children's stories -- Folklore